Flaxseed Prevents Interferon-alpha Induced Depressive Behavior in Mice: the α-Linolenic Acid is Essential - Azadeh Mesripour*; Maryam Almasi (Iranian Society of Pharmacognosy, 2021)
Background and objectives: Interferon-alpha (IFN-α) is a cytokine with various clinical applications, but it may induce depression by decreasing tryptophan level and producing neuroactive metabolites. Since Linum usitatissimum (flaxseed) is a valuable source for amino acids, α-linolenic acid (ALA), and lignans that could prevent inflammation and neurotoxicity, flaxseed effects on IFN-α induced depressant was evaluated. Methods: Flaxseed was applied either by whole ground flaxseeds in mice diet, or flaxseed oil by gavage feeding tube until effective antidepressant effects were observed. Seventy-eight male albino mice 25±3 g were used and divided in 13 groups, IFN-α 16×10 5 IU/kg was injected for 6 days. After the locomotor test, the forced swimming test (FST) was used to measure the immobility time indicating despair behavior, and the sucrose preference test measured anhedonia. Results: There were only marginal differences in the locomotor activity; however, the immobility time increased by IFN-α (154.5±11.22 s, vs control 121.3±7.14 s; p=0.031), and sucrose preference was 65% indicating depression. The administration of flaxseed 30% or flaxseed oil 25% with IFN-α significantly reduced the immobility time (92.67±11.60 s and 94.17±10.12 s, respectively, vs IFN-α normal diet, p <0.01), sucrose preference also increased that supported the antidepressant effect. Conclusion: Flaxseed could prevent IFN-α induced depressive-like behavior in mice. Although interpretation from animal to human studies needs careful attention, this study supports the use of flaxseed in the diet as reasonable strategy to prevent depression in high-risk individuals, such as patients treated with IFN-α.